1987
DOI: 10.2307/3577002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intestine and Bone Marrow Radiosensitivity of the BALB/c and the C57BL/6 Mouse Strains and Their B6CF 1 Offspring

Abstract: The radiosensitivity as measured by LD50/6 or LD50/30 of the F1 hybrid B6CF1 (C57BL/6 X BALB/c) is similar to that of C57BL/6 mice but markedly different from BALB/c. The LD50/6 for BALB/c mice was about 8.8 Gy compared to 16.4 Gy for the B6CF1. The difference in LD50/6 between the parent strains or between BALB/c and the F1 hybrid could not be explained by any differences in crypt cell number, cell cycle time, or transit time. Likewise, the observed differences in the LD50/6 do not appear to result from marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 8 publications
2
25
0
Order By: Relevance
“…Mouse strain differences in radiosensitivity and survival have been observed for over 50 years (Grahn and Hamilton 1956; Hanson et al 1987). These findings may represent innate differences, particularly in the immune response, but also the enteric flora population.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse strain differences in radiosensitivity and survival have been observed for over 50 years (Grahn and Hamilton 1956; Hanson et al 1987). These findings may represent innate differences, particularly in the immune response, but also the enteric flora population.…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45] Higher doses can cause the animals to die secondary to irradiation-induced toxicity while lower doses may prolong the time necessary to achieve sufficient donor engraftment. 44 Fifty-six 6-month-old C57BL/6 male mice were divided into two groups.…”
Section: Total Body Irradiationmentioning
confidence: 99%
“…Using only data points from 7.5 or 10 Gy and higher did not significantly decrease the D 0 in our study (data not shown). One possible explanation for the inter-study discrepancies could be variations in inherent radiosensitivity between different mouse strains [18]. Since radiation doses of 14 to 17 Gy lead to a near complete eradication of jejunal crypts, we chose to use only doses up to 10 Gy in the combined chemoradiation experiments.…”
Section: Discussionmentioning
confidence: 99%